A low-cost hard carbon material and its preparation method and application

By using biomass and ZnCl2·4H2O melt solution to dissolve cellulose, heat treatment and catalytic polymerization reaction, the final calcination treatment is used to obtain hard carbon material, which solves the problems of high preparation cost and complex process of existing hard carbon materials, and realizes the preparation of low-cost and high-performance hard carbon materials, which is suitable for the negative electrode material of sodium ion batteries.

CN117486198BActive Publication Date: 2025-03-25ZHUHAI NAGAN NEW ENERGY TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311462796.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-03
Publication Date
2025-03-25
Estimated Expiration
2043-11-03

AI Technical Summary

Technical Problem

The existing hard carbon material preparation methods are costly, complex in process, unenvironmental and unstable in raw materials, making it difficult to provide a sodium ion battery negative electrode material with low cost, simple process and excellent performance.

Method used

Biomass is used as raw material, and cellulose is dissolved through ZnCl2·4H2O melt solution, and then mixed with phosphorylation reagent for heat treatment. Then, phosphorylated cellulose is used to catalyze the polymerization and pre-carbonization reaction of C9 raw oil, waste plastic and biomass, and finally calcined in the protective gas to obtain hard carbon material.

Benefits of technology

It realizes the preparation of low-cost and high-performance hard carbon materials, with uniform particle size, stable properties, and excellent rate performance, and is suitable for the negative electrode material of sodium ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004533663010000121
    Figure BDA0004533663010000121
  • Figure BDA0004533663010000131
    Figure BDA0004533663010000131
Patent Text Reader

Abstract

The present invention belongs to the technical field of carbon-based material preparation, and provides a low-cost hard carbon material and a preparation method and application thereof. The method comprises the following steps: adding biomass to a zinc chloride hydrate melt to dissolve and obtain crude fibers; mixing the crude fibers with a mixed solution, filtering, washing and drying in sequence to obtain biomass cellulose; mixing the biomass cellulose with a phosphorylation agent and heat treating to obtain phosphorylated cellulose; using phosphorylated cellulose to catalyze C9 feedstock oil, waste plastics and biomass to perform polymerization and pre-carbonization reactions in sequence to obtain a hard carbon precursor; in a protective gas, calcining the hard carbon precursor to obtain a hard carbon material. The hard carbon material provided by the present invention has a large sodium ion embedding amount and a low raw material cost, which can reduce the cost of hard carbon materials and the cost per unit capacity of sodium ion batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of carbon-based material preparation, and in particular to a low-cost hard carbon material and a preparation method and application thereof. Background Art

[0002] When the size of a certain dimension of cellulose is reduced to less than 100nm, nano-scale cellulose is obtained, collectively referred to as nanocellulose. Nanocellulose not only has the basic structure and properties of cellulose, but also has nanoparticle characteristics such as small diameter and large specific surface area. Nanocellulose is abundant in source, easy to biodegrade, has good suitability, has excellent natural properties such as high elastic modulus and high aspect ratio, and also has high surface area to volume ratio, low density, thixotropy and optical properties, as well as good chemical stability, so it has potential value for high-end applications, such as flexible electronics, medical products, thermal integration, shape memory and energy materials.

[0003] At present, sodium-ion batteries are a new energy storage technology, and hard carbon is a mature negative electrode material for sodium-ion batteries. Hard carbon can be considered a general term for carbon that is difficult to graphitize. Its microstructure is a short-range ordered micro-region stacked by curved graphite-like sheets. Each micro-region is randomly and disorderly stacked, leaving a large number of nanopores. Because it often has a large interlayer spacing (usually greater than 0.37nm), more nanopores, and more defect sites, it can store more sodium ions. However, most of the current methods for preparing hard carbon materials have technical problems such as high cost and complex process, environmental pollution, and unstable source of raw materials for preparation.

[0004] Therefore, how to provide a sodium ion battery negative electrode material with low cost, simple process and excellent performance has become a problem that technicians in this field need to solve urgently. Summary of the invention

[0005] In view of this, the present invention provides a low-cost hard carbon material and a preparation method and application thereof, which aims to solve the technical problems of high cost and complex process in the preparation of existing hard carbon materials.

[0006] In order to achieve the above object, the present invention adopts the following technical solution:

[0007] The present invention provides a method for preparing a hard carbon material, comprising the following steps:

[0008] S1. Add biomass to ZnCl 2 ·4H 2 The crude fibers are dissolved in a molten solution to obtain crude fibers; the crude fibers are mixed with the mixed solution, and are filtered, washed and dried in sequence to obtain biomass cellulose;

[0009] S2, mixing the biomass cellulose with a phosphorylation reagent and then heat-treating the mixture to obtain phosphorylated cellulose;

[0010] S3, using phosphorylated cellulose to catalyze C9 raw oil, waste plastics and biomass to sequentially perform polymerization and pre-carbonization reactions to obtain a hard carbon precursor;

[0011] S4. In a protective gas, the hard carbon precursor is calcined to obtain a hard carbon material.

[0012] Furthermore, in step S1, the biomass and ZnCl 2 ·4H 2 The mass ratio of O melt is 1 to 10:100; the biomass is bagasse, bamboo powder or reed powder; the dissolution temperature is 50 to 80° C., and the dissolution time is 5 to 10 hours.

[0013] Furthermore, in step S1, the mixed solution comprises glacial acetic acid, sodium hypochlorite and water, and the mass volume ratio of the glacial acetic acid, sodium hypochlorite and water is 5-10 mL: 1-5 g: 200-300 mL;

[0014] The mass volume ratio of the crude fiber to the mixed solution is 1-10 g: 200-300 mL.

[0015] Furthermore, in step S2, the mass ratio of biomass cellulose to phosphorylation reagent is 30:70-120;

[0016] The phosphorylation reagent comprises urea, sodium dihydrogen phosphate dihydrate, phosphoric acid and water; the mass ratio of the urea, sodium dihydrogen phosphate dihydrate, phosphoric acid and water is 3-4:1-2:1-2:3-4.

[0017] Furthermore, in step S2, the heat treatment temperature is 60-200° C., and the heat treatment time is 0.5-3 h.

[0018] Furthermore, in step S3, the mass ratio of phosphorylated cellulose, C9 feedstock oil, waste plastics and biomass is 1:2-10:2-10:2-10; the polymerization reaction temperature is 60-120°C, and the polymerization reaction time is 2-5h; the pre-carbonization reaction temperature is 200-600°C, and the pre-carbonization reaction time is 2-5h;

[0019] The waste plastic is one or more of waste PET plastic, waste phenolic resin and waste polycarbonate plastic; the biomass powder is one or more of bagasse, bamboo powder and reed powder.

[0020] Furthermore, in step S4, the calcination temperature is 600-1600° C., the calcination time is 1-10 h, and the heating rate from room temperature to the calcination temperature is 1-10° C. / min.

[0021] Furthermore, in step S4, the protective gas is nitrogen, argon or carbon dioxide.

[0022] The present invention provides a hard carbon material prepared by the above preparation method.

[0023] The present invention also provides application of the hard carbon material in sodium ion batteries.

[0024] It can be seen from the above technical solution that compared with the prior art, the beneficial effects of the present invention are as follows:

[0025] The present invention uses biomass as a raw material to prepare a catalyst that can catalyze the polymerization reaction of C9 raw oil, which has the advantages of wide source, low cost and no pollution, and the catalyst will not corrode the equipment;

[0026] Since aqueous solution has a weak reaction with hydrogen bonds, it is difficult to destroy the structure of cellulose and lignin in biomass, and ZnCl 2 ·4H 2 The O melt contains metal ions, which can enhance the depolymerization ability of the compound aqueous solution on cellulose, lignin and hemicellulose. Therefore, the present invention uses ZnCl 2 ·4H 2 The melt dissolves cellulose and the pretreatment step of biomass is omitted.

[0027] The present invention transforms a hard carbon precursor into a high-performance hard carbon negative electrode material for a sodium ion battery through a simple heat treatment method. The material has uniform particle size, stable properties and excellent rate performance. DETAILED DESCRIPTION

[0028] The present invention provides a method for preparing a low-cost hard carbon material, comprising the following steps:

[0029] S1. Add biomass to ZnCl 2 ·4H 2 The crude fibers are dissolved in a molten solution to obtain crude fibers; the crude fibers are mixed with the mixed solution, and are filtered, washed and dried in sequence to obtain biomass cellulose;

[0030] S2, mixing the biomass cellulose with a phosphorylation reagent and then heat-treating the mixture to obtain phosphorylated cellulose;

[0031] S3, using phosphorylated cellulose to catalyze C9 raw oil, waste plastics and biomass to sequentially perform polymerization and pre-carbonization reactions to obtain a hard carbon precursor;

[0032] S4. In a protective gas, the hard carbon precursor is calcined to obtain a hard carbon material.

[0033] In the present invention, in step S1, biomass and ZnCl 2 ·4H 2 The mass ratio of O melt is 1 to 10:100, preferably 3 to 9:100, and more preferably 6 to 8:100; the biomass is bagasse, bamboo powder or reed powder, preferably bagasse or reed powder, and more preferably bagasse;

[0034] The dissolution temperature is 50 to 80° C., preferably 55 to 75° C., and more preferably 60 to 70° C.; the dissolution time is 5 to 10 hours, preferably 6 to 9 hours, and more preferably 7 to 8 hours.

[0035] In the present invention, in step S1, the mixed solution comprises glacial acetic acid, sodium hypochlorite and water, and the mass volume ratio of the glacial acetic acid, sodium hypochlorite and water is 5-10 mL: 1-5 g: 200-300 mL, preferably 6-9 mL: 2-4 g: 220-280 mL, and more preferably 7-8 mL: 3 g: 240-260 mL;

[0036] The mass volume ratio of the crude fiber to the mixed solution is 1-10 g: 200-300 mL, preferably 2-8 g: 220-280 mL, and more preferably 4-6 g: 240-260 mL.

[0037] In the present invention, in step S2, the mass ratio of biomass cellulose to phosphorylation reagent is 30:70-120, preferably 30:80-110, and more preferably 30:90-100;

[0038] The phosphorylation reagent comprises urea, sodium dihydrogen phosphate dihydrate, phosphoric acid and water; the mass ratio of urea, sodium dihydrogen phosphate dihydrate, phosphoric acid and water is 3-4:1-2:1-2:3-4, preferably 3.2-3.8:1.2-1.8:1.2-1.8:3.2-3.8, and more preferably 3.4-3.6:1.4-1.6:1.4-1.6:3.4-3.6.

[0039] In the present invention, in step S2, the heat treatment temperature is 60-200°C, preferably 80-180°C, and more preferably 100-150°C; the heat treatment time is 0.5-3h, preferably 1-2.5h, and more preferably 1.5-2h.

[0040] In the present invention, in the step S3, the mass ratio of phosphorylated cellulose, C9 feedstock oil, waste plastic and biomass is 1:2-10:2-10:2-10, preferably 1:3-7:3-7:3-7, and more preferably 1:4-6:4-6:4-6; the temperature of the polymerization reaction is 60-120°C, preferably 80-110°C, and more preferably 90-100°C; the time of the polymerization reaction is 2-5h, preferably 3-4h, and more preferably 3.5h; the temperature of the pre-carbonization reaction is 200-600°C, preferably 250-500°C, and more preferably 300-400°C; the time of the pre-carbonization reaction is 2-5h, preferably 3-4h, and more preferably 3.5h;

[0041] The waste plastic is one or more of waste PET plastic, waste phenolic resin and waste polycarbonate plastic, preferably PET plastic and / or waste phenolic resin, and more preferably PET plastic; the biomass powder is one or more of bagasse, bamboo powder and reed powder, preferably bagasse and / or bamboo powder, and more preferably bagasse.

[0042] In the present invention, in step S4, the calcination temperature is 600-1600°C, preferably 800-1500°C, and more preferably 1000-1200°C; the calcination time is 1-10h, preferably 2-8h, and more preferably 4-6h; the heating rate from room temperature to the calcination temperature is 1-10°C / min, preferably 2-8°C / min, and more preferably 3-7°C / min.

[0043] In the present invention, in step S4, the protective gas is nitrogen, argon or carbon dioxide, preferably nitrogen or argon, and more preferably nitrogen.

[0044] The present invention provides a hard carbon material prepared by the above preparation method.

[0045] The present invention also provides application of the hard carbon material in sodium ion batteries.

[0046] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0047] Example 1

[0048] Adding bagasse to ZnCl 2 ·4H 2O melt at 60 ° C for 7 h to obtain crude fiber, in which bagasse and ZnCl 2 ·4H 2 The mass volume ratio of the molten liquid is 6:100; the crude fiber is mixed with a mixed solution of glacial acetic acid, sodium hypochlorite and water, and then filtered, washed and dried in sequence to obtain sugarcane cellulose, wherein the mass volume ratio of glacial acetic acid, sodium hypochlorite and water is 7mL:2g:250mL, and the mass volume ratio of the crude fiber to the mixed solution is 5g:250mL;

[0049] 32 g of urea, 17 g of sodium dihydrogen phosphate dihydrate, 17 g of phosphoric acid and 34 g of water are mixed to obtain a phosphorylation reagent, 30 g of sugarcane cellulose is added to the phosphorylation reagent, and heat-treated at 80° C. for 2.5 h to obtain phosphorylated cellulose;

[0050] Weigh 100g of C9 raw oil, 100g of waste PET plastic, and 100g of bagasse and place them in a three-necked flask with circulating condensed water and mechanical stirring, start stirring, add 50g of phosphorylated cellulose catalyst, polymerize at 120°C for 2 hours, raise the temperature to 150°C after the polymerization is completed, distill the polymer solution to recover toluene, and raise the temperature to 350°C and keep it for 2 hours to perform a pre-carbonization reaction to obtain a hard carbon precursor;

[0051] In a nitrogen atmosphere, the hard carbon precursor was put into a calcining furnace. The heating rate in the calcining furnace was 10°C / min. The temperature of the calcining furnace was set to 1600°C. The hard carbon material was obtained after calcining for 5 hours.

[0052] Example 2

[0053] Add bamboo powder to ZnCl 2 ·4H 2 O melt at 80 ° C for 5 h to obtain crude fiber, in which bamboo powder and ZnCl 2 ·4H 2 The mass volume ratio of the molten liquid is 8:100; the crude fiber is mixed with a mixed solution of glacial acetic acid, sodium hypochlorite and water, and then filtered, washed and dried in sequence to obtain bamboo cellulose, wherein the mass volume ratio of glacial acetic acid, sodium hypochlorite and water is 6mL:3g:260mL, and the mass volume ratio of the crude fiber to the mixed solution is 4g:260mL;

[0054] 35 g of urea, 10 g of sodium dihydrogen phosphate dihydrate, 15 g of phosphoric acid and 40 g of water were mixed to obtain a phosphorylation reagent, 30 g of bamboo cellulose was added to the phosphorylation reagent, and heat-treated at 100° C. for 2 h to obtain phosphorylated cellulose;

[0055] Weigh 100g of C9 raw material oil, 100g of waste polycarbonate, and 100g of bamboo powder and place them in a three-necked flask with circulating condensed water and mechanical stirring, start stirring, add 20g of phosphorylated cellulose catalyst, polymerize at 110°C for 3 hours, raise the temperature to 150°C after the polymerization is completed, distill the polymer solution to recover toluene, and after the recovery of toluene, raise the temperature to 200°C and keep it for 3 hours for pre-carbonization reaction to obtain a hard carbon precursor;

[0056] In a nitrogen atmosphere, the hard carbon precursor was put into a calcining furnace. The heating rate in the calcining furnace was 5°C / min. The temperature of the calcining furnace was set to 1500°C. The hard carbon material was obtained by calcining for 3 hours.

[0057] Example 3

[0058] Add reed powder to ZnCl 2 ·4H 2 O melt at 50 ° C for 8 h to obtain crude fiber, in which reed powder and ZnCl 2 ·4H 2 The mass volume ratio of the crude fiber to the mixed solution of acetic acid, sodium hypochlorite and water is 3:100; the crude fiber is mixed with a mixed solution of acetic acid, sodium hypochlorite and water, and then filtered, washed and dried in sequence to obtain reed cellulose, wherein the mass volume ratio of acetic acid, sodium hypochlorite and water is 2mL:1g:200mL, and the mass volume ratio of the crude fiber to the mixed solution is 2g:200mL;

[0059] 30 g of urea, 20 g of sodium dihydrogen phosphate dihydrate, 15 g of phosphoric acid and 35 g of water were mixed to obtain a phosphorylation reagent, 30 g of reed cellulose was added to the phosphorylation reagent, and heat-treated at 100° C. for 2 h to obtain phosphorylated cellulose;

[0060] Weigh 100g of C9 raw material oil, 20g of phenolic resin, and 20g of reed powder in a three-necked flask with circulating condensed water and mechanical stirring, start stirring, add 40g of phosphorylated cellulose catalyst, polymerize at 100°C for 2 hours, raise the temperature to 150°C after the polymerization is completed, distill the polymer solution to recover toluene, raise the temperature to 600°C after the recovery of toluene, and keep it warm for 2 hours for pre-carbonization reaction to obtain a hard carbon precursor;

[0061] In a nitrogen atmosphere, the hard carbon precursor was put into a calcining furnace. The heating rate in the calcining furnace was 8°C / min. The temperature of the calcining furnace was set to 1600°C. The hard carbon material was obtained by calcining for 6 hours.

[0062] Comparative Example 1

[0063] Adding bagasse to ZnCl 2 ·4H 2O melt at 60 ° C for 7 h to obtain crude fiber, in which bagasse and ZnCl 2 ·4H 2 The mass volume ratio of the molten liquid is 12:100; the crude fiber is mixed with a mixed solution of glacial acetic acid, sodium hypochlorite and water, and then filtered, washed and dried in sequence to obtain sugarcane cellulose, wherein the mass volume ratio of glacial acetic acid, sodium hypochlorite and water is 4mL:6g:180mL, and the mass volume ratio of the crude fiber to the mixed solution is 12g:180mL;

[0064] 32 g of urea, 17 g of sodium dihydrogen phosphate dihydrate, 17 g of phosphoric acid and 34 g of water are mixed to obtain a phosphorylation reagent, 30 g of sugarcane cellulose is added to the phosphorylation reagent, and heat-treated at 80° C. for 2.5 h to obtain phosphorylated cellulose;

[0065] Weigh 100 g of C9 raw material oil into a three-necked flask with circulating condensed water and magnetic stirring, start stirring, add 100 g of phosphorylated cellulose catalyst, polymerize at 90°C for 2 hours, raise the temperature to 150°C after the polymerization is completed, distill the polymerization liquid to recover toluene, and obtain a hard carbon precursor;

[0066] In a nitrogen atmosphere, the hard carbon precursor was put into a calcining furnace. The heating rate in the calcining furnace was 10°C / min. The temperature of the calcining furnace was set to 1800°C. The hard carbon material was obtained after calcining for 5 hours.

[0067] Comparative Example 2

[0068] Add bamboo powder to ZnCl 2 ·4H 2 O melt at 60 ° C for 7 h to obtain crude fiber, in which bamboo powder and ZnCl 2 ·4H 2 The mass ratio of the melt is 0.8:100; the crude fiber is mixed with a mixed solution of glacial acetic acid, sodium hypochlorite and water, and then filtered, washed and dried in sequence to obtain bamboo cellulose, wherein the mass volume ratio of glacial acetic acid, sodium hypochlorite and water is 7mL:2g:250mL, and the mass volume ratio of the crude fiber to the mixed solution is 5g:250mL;

[0069] 35 g of urea, 10 g of sodium dihydrogen phosphate dihydrate, 15 g of phosphoric acid and 40 g of water were mixed to obtain a phosphorylation reagent, 30 g of bamboo cellulose was added to the phosphorylation reagent, and heat-treated at 100° C. for 2 h to obtain phosphorylated cellulose;

[0070] Weigh 100 g of C9 raw material oil into a three-necked flask with circulating condensed water and magnetic stirring, start stirring, add 50 g of phosphorylated cellulose catalyst, polymerize at 120°C for 1 hour, raise the temperature to 150°C after the polymerization is completed, distill the polymerization liquid to recover toluene, and obtain a hard carbon precursor;

[0071] In a nitrogen atmosphere, the hard carbon precursor was put into a calcining furnace. The heating rate in the calcining furnace was 10°C / min. The temperature of the calcining furnace was set to 800°C. The hard carbon material was obtained by calcining for 10 hours.

[0072] Comparative Example 3

[0073] Add reed powder to ZnCl 2 ·4H 2 O melt at 60 ° C for 7 h to obtain crude fiber, in which reed powder and ZnCl 2 ·4H 2 The mass volume ratio of the crude fiber to the mixed solution of acetic acid, sodium hypochlorite and water is 6:100; the crude fiber is mixed with a mixed solution of acetic acid, sodium hypochlorite and water, and then filtered, washed and dried in sequence to obtain reed cellulose, wherein the mass volume ratio of acetic acid, sodium hypochlorite and water is 7mL:2g:250mL, and the mass volume ratio of the crude fiber to the mixed solution is 15g:250mL;

[0074] 30 g of urea, 20 g of sodium dihydrogen phosphate dihydrate, 15 g of phosphoric acid and 35 g of water were mixed to obtain a phosphorylation reagent, 30 g of reed cellulose was added to the phosphorylation reagent, and heat-treated at 100° C. for 2 h to obtain phosphorylated cellulose;

[0075] Weigh 110 g of C9 raw material oil into a three-necked flask with circulating condensed water and magnetic stirring, start stirring, add 10 g of phosphorylated cellulose catalyst, polymerize at 90°C for 2 hours, raise the temperature to 150°C after the polymerization is completed, distill the polymerization liquid to recover toluene, and obtain a hard carbon precursor;

[0076] In a nitrogen atmosphere, the hard carbon precursor was put into a calcining furnace. The heating rate in the calcining furnace was 10°C / min. The temperature of the calcining furnace was set to 1800°C. The hard carbon material was obtained after calcining for 5 hours.

[0077] Performance Testing

[0078] The hard carbon material, carbon nanotubes and sodium carboxymethyl cellulose were compounded in a mass ratio of 90:5:5 as the positive electrode, metallic sodium as the negative electrode, 15 μm thick PE as the separator, 1:1 volume ratio of propylene carbonate / diethyl carbonate solution as the electrolyte, fluoroethylene carbonate as the electrolyte additive (the molar ratio of the additive to the electrolyte was 1:20), and NaPF 6The concentration was 1.5 mol / L. The hard carbon battery was assembled in a glove box filled with hydrogen for charge and discharge tests. The charge and discharge rate was 0.1C (voltage range 0-2V). The test results of 0.1C first efficiency, 0.1C gram capacity, cycle performance and rate performance are shown in Table 1.

[0079] Table 1 Performance test results of embodiments and comparative examples

[0080]

[0081]

[0082] It can be seen from Table 1 that within the technical parameter range of the present invention, the prepared hard carbon material has excellent rate performance as the negative electrode material of the sodium ion battery.

[0083] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a low-cost hard carbon material, characterized in that: The following steps are involved: S1. adding biomass into ZnCl2·4H2O melt to dissolve and obtain crude fiber; mixing the crude fiber with the mixed solution, filtering, washing and drying in sequence to obtain biomass cellulose; S2, mixing the biomass cellulose with a phosphorylation reagent and then heat-treating the mixture to obtain phosphorylated cellulose; S3, using phosphorylated cellulose to catalyze C9 raw oil, waste plastics and biomass powder to sequentially perform polymerization and pre-carbonization reactions to obtain a hard carbon precursor; S4, calcining the hard carbon precursor in a protective gas to obtain a hard carbon material; In step S1, the mixed solution comprises glacial acetic acid, sodium hypochlorite and water, and the mass volume ratio of the glacial acetic acid, sodium hypochlorite and water is 5-10 mL: 1-5 g: 200-300 mL.

2. The preparation method according to claim 1, characterized in that: In the step S1, the mass ratio of biomass to ZnCl2·4H2O melt is 1-10:100; the biomass is bagasse, bamboo powder or reed powder; the dissolution temperature is 50-80°C, and the dissolution time is 5-10 hours.

3. The preparation method according to claim 2, characterized in that: The mass volume ratio of the crude fiber to the mixed solution is 1-10 g: 200-300 mL.

4. The preparation method according to claim 1 or 3, characterized in that: In the step S2, the mass ratio of biomass cellulose to phosphorylation reagent is 30:70-120; The phosphorylation reagent comprises urea, sodium dihydrogen phosphate dihydrate, phosphoric acid and water; the mass ratio of the urea, sodium dihydrogen phosphate dihydrate, phosphoric acid and water is 3-4:1-2:1-2:3-4.

5. The preparation method according to claim 4, characterized in that: In step S2, the heat treatment temperature is 60-200° C., and the heat treatment time is 0.5-3 h.

6. The preparation method according to claim 1, 2 or 5, characterized in that: In the step S3, the mass ratio of phosphorylated cellulose, C9 raw material oil, waste plastic and biomass powder is 1:2~10:2~10:2~10; the temperature of the polymerization reaction is 60~120°C, and the time of the polymerization reaction is 2~5h; the temperature of the pre-carbonization reaction is 200~600°C, and the time of the pre-carbonization reaction is 2~5h; The waste plastic is one or more of waste PET plastic, waste phenolic resin and waste polycarbonate plastic; the biomass powder is one or more of bagasse, bamboo powder and reed powder.

7. The preparation method according to claim 6, characterized in that: In the step S4, the calcination temperature is 600-1600° C., the calcination time is 1-10 h, and the heating rate from room temperature to the calcination temperature is 1-10° C. / min.

8. The preparation method according to claim 1, 5 or 7, characterized in that: In step S4, the protective gas is nitrogen, argon or carbon dioxide.

9. The hard carbon material prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the hard carbon material according to claim 9 in sodium ion batteries.

Citation Information

Patent Citations

  • Phosphorylated cellulose nanofiber / black phosphorus quantum dot composite flame-retardant film and preparation method thereof

    CN112321861A

  • Biomass hard carbon manufacturing method and sodium ion battery negative electrode thereof

    CN113224264A